The Oxford handbook of oral history - Ritchie, Donald A. 1945- Hrsg (Oxford Univ. Press, 2011)
The dynamics of interviewing / Mary Kay Quinlan -- Those who prevailed and those who were replaced : interviewing on both sides of a conflict / Miroslav Vaněk -- Interviewing in cross-cultural settings / William Schneider -- Case study : oral history and democracy : lessons from illiterates / Mercedes Vilanova -- Memory and remembering in oral history / Alistair Thomson -- Can memory be collective ? / Anna Green -- Case study : Rome's house memory and history : the politics of memory and public institutions / Alessandro Portelli -- How does one win a lost war? Oral history and political memories / Federico Guillermo Lorenz -- Disappointed remains : trauma, testimony, and reconciliation in post-apartheid South Africa / Sean Field -- Case study : memory work with children affected by HIV/AIDS in South Africa / Philippe Denis -- The stages of women's oral history / Sue Armitage -- Race and oral history / Albert S. Broussard -- Remembering in later life : generating individual and social change / Joanna Bornat -- The Proust effect : oral history and the senses / Paula Hamilton -- After action : oral history and war / Megan Hutching -- Case study : "Above all, we need the witness" : the oral history of Holocaust survivors / Jessica Wiederhorn -- Case study : field notes on catastrophe : reflections on The September 11, 2001, Oral History Memory and Narrative Project / Mary Marshall Clark -- Doing video oral history / Brien R. Williams -- Case study : opening up memory space : the challenges of audiovisual history / Albert Lichtblau -- Achieving the promise of oral history in a digital age / Doug Boyd -- Oral history : media, message, and meaning / Clifford M. Kuhn -- Messiah with a microphone? Oral historians, technology, and sound archives / Robert B. Perks -- Case study : between the raw and the cooked in oral history : notes from the kitchen / Michael Frisch and Douglas Lambert -- The legal ramifications of oral history / John A. Neuenschwander -- Medical ethics and oral history / Michelle Winslow and Graham Smith -- The archival imperative : can oral history survive the funding crisis in archival institutions? / Beth M. Robertson -- Case study : The Southern Oral History Program / Jacquelyn Dowd Hall, interviewed by Kathryn Nasstrom -- Case study : what is it that university-based oral history can do? The Berkeley experience / Richard Cándida Smith -- Toward A public oral history / Graham Smith -- Motivating the twenty-first-century student with oral history / Glenn Whitman -- Oral history in universities : from margins to mainstream / Janis Wilton -- Case study : engaging interpretation through digital technologies / Rina Benmayor -- Oral history in the digital age / Kelly Schrum, Sheila Brennan, James Halabuk, Sharon M. leon, and Tom Scheinfeldt